Pengembangan Sistem Informasi Pengelolaan Toko Elektronik berbasis Web dengan Menerapkan Pola Perancangan MVC (Studi Kasus : Toko Indah Elektronik) - Muhammad Galang Tarigan; Denny Sagita Rusdianto; Eriq Muhammad Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Toko Indah Elektronik is a store that runs a business in the electronics sector, domiciled in Medan, North Sumatra. Not only selling electronic goods, this shop also provides repair services for electronic goods such as washing machines, refrigerators, televisions, and others. Currently, Indah Elektronik store wants to improve service and work efficiency in terms of time and energy. This is done because as the store develops, the current business processes cause problems such as a lack of work efficiency in terms of time and effort. This happens because of the management and archiving of sales transaction data, the management of goods is not good. On the other hand, archiving sales data that is not good causes problems with financial records, sometimes there are some sales that are not recorded, so it is not known exactly how much income and expenses each month from the existing archives. Therefore, to improve the services in the store and efforts to solve existing problems, a web-based electronic store management information system was created by applying the MVC (Model-View-Controller) design pattern with the main feature being to facilitate the sales transaction process, management goods, recording sales and financial transactions. The system development process uses the waterfall development model. Implementation of the system developed using the Laravel framework. The developed system has been tested using unit testing, integration, validation and compatibility strategies to produce values with valid status.